Have the Findings from Clinical Risk Prediction and Trials Any Key Messages for Safety Pharmacology? - Lane, Jem D.; Tinker, Andrew (Frontiers in Physiology, 2017)
Anti-arrhythmic drugs are a mainstay in the management of symptoms related to arrhythmias, and are adjuncts in prevention and treatment of life-threatening ventricular arrhythmias. However they also have the potential for pro-arrhythmia and thus the prediction of arrhythmia predisposition and drug response are critical issues. Clinical trials are the latter stages in the safety testing and efficacy process prior to market release, and as such serve as a critical safeguard. In this review, we look at some of the lessons to be learned from approaches for arrhythmia prediction in patients, clinical trials of drugs used in the treatment of arrhythmias, and the lessons for pre-clinical safety pharmacology testing.